Enigma : a magical mystery - Base, Graeme (New York, NY : Abrams Books for Young Readers, 2008)
When Bertie the badger visits his grandfather at a retirement home for magicians, he learns that his grandfather's rabbit, Enigma, has disappeared along with everyone's magical things, and the reader is invited to help break a code to find the items hidden throughout the book. Includes a built-in decoder.
Keywords: Stories in rhyme; Magicians -- Juvenile fiction; Theft -- Juvenile fiction; Grandfathers -- Juvenile fiction; Animals -- Juvenile fiction; Code and cipher stories; Picture puzzles -- Juvenile fiction; Stories in rhyme; Magicians -- Fiction; Stealing -- Fiction; Grandfathers -- Fiction; Badgers -- Fiction; Rabbits -- Fiction; Ciphers -- Fiction; Picture puzzles